CLINICAL VALUE OF METFORMIN IN APPLICATION AGAINST DIABETES AND OBESITY IN CHILDREN AND TEENAGERS - E.E. Petryaikina; M.B. Antsiferov; O.V. Dukhareva; A.I. Novitskaya; L.G. Dorofeeva; E.A. Pronina; I.G. Rybkina; T.D. Mikhailova; E.T. Mandzhieva; I.G. Garyaeva (Педиатрическая фармакология, 2009)
The Type 1 and Type 2 diabetes mellitus spread is growing up among children. This article highlights the data on the disease epidemiology, etiology, risk factors of the progression, clinical run and complications. Special attention is paid to the obesity as a condition, which most often accompanies insulin resistance and diabetes formation; the authors consider also prevention opportunities. The tactics of the management of patient with the said pathology is also highlighted here.Key words: diabetes, insulin resistance, disturbed tolerance to glucose, obesity, treatment, children.